The impact of job burnout and cyberloafing on company performance: The mediating role of employee performance - Irma Yunita; Dedeh Jubaedah; Sutra Nahraeni (Indonesia Auditing Research Journal, 2026)
This study aims to examine the effect of job burnout and cyberloafing on company performance, with employee performance serving as a mediating variable. The research was conducted at KPKNL Serang and involved 44 respondents selected through total sampling. A quantitative approach was employed using a Likert-scale questionnaire, while data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0. The results show that job burnout has a negative and significant effect on employee performance. In addition, employee performance has a positive and significant effect on company performance and significantly mediates the effect of job burnout on company performance. However, cyberloafing does not have a significant effect on either employee performance or company performance, and it is also not mediated by employee performance. These findings highlight the importance of managing job burnout to improve employee productivity and overall company performance.